A qualidade social como conttraposição à qualidade total: reflexões de Pablo Gentili - Araujo, Marta Maria; Cabral Neto, Antônio; Almeida, Maria Doninha de (Revista Educação em Questão, 1998)
A qualidade social como conttraposição à qualidade total: reflexões de Pablo Gentili